Legal Consequences of Fiduciary Registration Over Time - Sanusi, Sanusi; Artadi, Ibn; Nurhaqi, Ari (Budapest International Research and Critics University, 2021)
The needs and desperateness of the community in its economy make the transaction also buy goods with the object of buying and selling vehicles that are used as objects of fiduciary guarantee. Vehicle / object of fiduciary guarantee in can be credited to the financing/ leasing institution with payment in installments. Against guarantees for repayment of the financing is charged guaranteed in a fiduciary. In practice the transfer of the fiduciary guarantee without being known by the financing institution. Even though the transfer or sale and purchase of the fiduciary guarantee object must be registered in advance to the Fiduciary Registration Office. This resulted in the emergence of cases that can be punished debtor. The problem is how the legal consequences for debtors who sell fiduciary guarantees with late registration and how tosettle against creditors who sell the fiduciary guarantee. The approach method used is the empirical juridical approach, the research is analytically descriptive, the approach is used to analyze qualitatively. Regarding the legal consequences of transferring fiduciary guarantee objects that are transferred or sold to another party.Â The right of creditors to get repayment on the loans granted is not lost even if it results from the invalidity of the fiduciary guarantee certificate, but results in creditors no longer having preferent rights. Law Enforcement through the means of criminal law is delayed, so there is no discussion, whether in this case there is a criminal act in the form of diverting, pawning or renting goods that become objects that become fiduciary guarantees without the permission of fiduciary recipients as referred to in Article 23 Jo Article 36 of Ri Law No. 42 of 1999 concerning Fiduciary Guarantee allegedly carried out by WARMO Bin (alm) CARWANbrothers.Â